The Influence of Strip Story Media on Learning Outcomes and Collaboration Skills of Junior High School Students - Ikhsan, Ramadhanul; Hadeli, Hadeli; Hasnah, Radhiatul (Ahlussunnah: Journal of Islamic Education, 2025)
This study aims to determine the effect of strip stoty media on students' learning outcomes and collaboration skills in the Al-Qur'an Hadith subject at Mtsn 6 Agam. This study uses a quantitative experimental method with a research design. posttest only group design. The population consisted of 10 classes from class VII 1 to VII 10 with the sampling technique using the techniqueclaster random sampling.The sample consists of class VII 3 as the control class and VII 4 as the experimental class. The data source was taken from the control class and the experimental class totaling 64 students through the provision of learning outcome tests and filling out questionnaires. The data were analyzed using descriptive statistical analysis and independent sample t-test using SPSS version 23. The results of the learning outcome test analysis showed an average of 76.88 for the control class, an average of 85.47 for the experimental class, and an independent sample t-test of 0.000 <0.05, which means there is an influence of strip story media on the learning outcomes of the Qur'an at MTsN 6 Agam. The results of the collaboration ability test analysis showed an average of 73.31 for the control class, an average of 83.06 for the experimental class, and an independent sample t-test of 0.001 <0.05, which means there is an influence of strip story media on the learning outcomes of the Qur'an at MTsN 6 Agam. The results of this study can be used as initial data for subsequent researchers in examining this problem in different contexts and issues.